Publications Received (Academy of Management Review, 2002)
The article presents a list of publications received, including: “Acquisition Strategy and Implementation,” by Nancy Hubbard, “Analyzing the Labor Force: Concepts. Measures, and Trends,” by Clifford C. Clogg, Scott R. Eliason, and Kevin T. Leicht, and “The Answer to How Is Yes: Acting on What Matters,” by Peter Block.